Heating-Enhanced Dielectrophoresis for Aligned Single-Walled Carbon Nanotube Film of Ultrahigh Density - Gu, Qingyuan (Nanoscale Res Lett, 2017)
In this paper, we demonstrate that the alignment density of individualized single-walled carbon nanotubes (SWCNTs) can be greatly improved by heating-enhanced dielectrophoresis (HE-DEP) process. The observations by scanning electron microscope (SEM) suggest ultrahigh alignment density and good alignment quality of SWCNTs. The intuitive alignment density of individualized SWCNTs is much higher than the currently reported best results. The reason of this HE-DEP process is explained by simulation work and ascribed to the heating-enhanced convection process, and the “convection force” induced by the heating effect is assessed in a novel way.